Perancangan dan Implementasi Sistem Penerimaan Murid Baru (SPMB) - Muhammad Yunus Rangkuti; Roxi Ivansyah Hardianto; Zulfa Bahrul Akmal; Adit Setyawan (Jurnal Riset Informatika dan Inovasi, 2026)
Student admission is a crucial administrative process in educational institutions that requires accuracy, efficiency, and transparency. However, many schools still rely on manual procedures, which often lead to data processing delays and recording errors. This study aims to design and develop a web-based Student Admission System (SPMB) to support an integrated registration and data management process. The research method includes system requirements analysis, system design, and application implementation. The results indicate that the developed system improves the efficiency of the admission process, simplifies applicant data management, and provides more accurate and accessible information. Therefore, the proposed system is expected to enhance the quality of administrative services in schools.